Makna Kata Sabar dalam Kajian Tafsir Maudhu’i - Imam Mujaddid Alhakimi; Dzulkifli Hadi Imawan (Nizham Jurnal Studi Keislaman, 2023)
Abstract One of the purposes behind the revelation of the Qur'an is to serve as a guiding light for humanity. However, the content of the Qur'an, including its verses and passages, often possesses a universal nature, necessitating specialized expertise in interpreting it through various methodologies, among which is the maudhu'i interpretation. The term "patience," as an illustration, is prominently present in numerous verses of the Qur'an, expressed in diverse linguistic forms. This term is frequently associated with other concepts such as 'iffah (self-restraint), hilm (forbearance), qana'ah (contentment), and zuhud (asceticism). Beyond these facets, patience embodies a disposition of embracing all provisions from God, encompassing both favorable and unfavorable circumstances. Even in the realm of blessings that originate from the divine, a sense of patience is indispensable, mirroring the patience demonstrated in acts of devotion. For instance, when an individual diligently engages in acts of worship like prayer and fasting, the essence of patience extends to persistently upholding these acts, notwithstanding the array of temptations that might undermine one's commitment. Keyword: Patient, Interpretation, Maudhu’i Abstrak Salah satu sebab diturunkannya al-Qur’an adalah sebagai petunjuk bagi umat manusia. Akan tetapi, ayat dan surat yang terkandung di dalam al-Qur’an adakalanya bersifat global, sehingga dibutuhkanlah keahlian dari menafsirkan al-Qur’an dengan berbagai metode, salah satunya dengan tafsir maudhu’i. Kata sabar dalam al-Qur’an contohnya, terdapat banyak dalam ayat-ayat al-Qur’an dalam berbagai bentuk kata. Kata sabar juga sering diidentifikasikan sama dengan kata ‘iffah, hilm, qana’ah dan zuhud. Terlepas dari semua itu, sabar merupakan sikap menerima semua ketentuan Allah, baik itu ketentuan baik maupun ketentuan buruk. Karena dalam hal baik yang dikaruniakan Allah pun kita juga harus bersabar, seperti halnya sabar dalam ketaatan. Ketika seseorang sudah berbuat taat dalam beribadah, contohnya dalam shalat dan berpuasa, maka konsep sabar yang harus dilaksanakan adalah senantiasa berupaya untuk konsisten dalam menjaga ketaatan tersebut, meskipun terdapat berbagai macam godaan yang akan melemahkan taatnya seseorang tersebut. Keyword: Sabar, Tafsir, Maudhu’i